2008
DOI: 10.1111/j.1365-2133.2008.08686.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of infliximab on psoriatic nails: an unblinded, nonrandomized, open-label study

Abstract: Alphalthough there is no control group, this data suggests that infliximab is effective for psoriatic nail disease in the context of severe skin and joint involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 15 publications
(17 reference statements)
1
57
0
2
Order By: Relevance
“…The advent of high-resolution imaging in man to explore the nail, coupled with emerging immunogenetics and therapies, holds the key to a better understanding of nail disease and indeed systemic disorders that afflict the nail in man. The emerging data showing excellent response of psoriatic nail disease to anti-TNF therapies [44,45,46] that act principally on the innate arm of the immune response further support the idea of local innate immune responses in the nail-enthesis-bone apparatus as underscoring disease mechanisms at that site.…”
Section: Discussionmentioning
confidence: 88%
“…The advent of high-resolution imaging in man to explore the nail, coupled with emerging immunogenetics and therapies, holds the key to a better understanding of nail disease and indeed systemic disorders that afflict the nail in man. The emerging data showing excellent response of psoriatic nail disease to anti-TNF therapies [44,45,46] that act principally on the innate arm of the immune response further support the idea of local innate immune responses in the nail-enthesis-bone apparatus as underscoring disease mechanisms at that site.…”
Section: Discussionmentioning
confidence: 88%
“…An unblinded, non-randomised, open-label study of infliximab in 18 patients with nail psoriasis noted significant improvement in NAPSI scores after the third infusion of infliximab (week 14) [51]. A 47% reduction in mean NAPSI score was evident at week 14, and at week 38 (after 6 infusions), a 94% reduction in mean NAPSI score was evident, representing almost complete resolution of psoriatic nail involvement [51].…”
Section: The Advent Of New Treatment Options With Biologic Therapymentioning
confidence: 99%
“…Several trials and case reports have demonstrated that infliximab, a TNF inhibitor administered intravenously, provides significant improvement in patients with moderate to severe psoriasis with nail involvement [48,49,50,51]. …”
Section: The Advent Of New Treatment Options With Biologic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have demonstrated that biologicals such as tumor necrosis factor (TNF) antagonists (etanercept [7], infliximab [8,9]) may have significant influence on psoriatic nail disease. Adalimumab is a fully human IgG1 monoclonal antibody of the IgG1 isotype that binds to human TNF-α with high affinity and specificity, suppressing TNF-associated biologic responses by blocking its interaction with the p55 and p75 cell surface TNF receptors [10].…”
Section: Introductionmentioning
confidence: 99%